Pressurized Liquid Extraction and HPLC Analysis for Determination of Polyphenols in Tobacco - Chen, Zhiyan; Huang, Shijie; Su, Qingde; Zhu, Xiaolan (Asian Journal of Chemistry, 2013)
A simple and efficient pressurized liquid extraction followed by HPLC analysis method has been investigated for the extraction of polyphenols in tobacco. After pressurized liquid extraction and C18 disposable cartridge solid-phase extraction clean-up, to reduce the co-extraction of interference, polyphenols (chlorogenic acid, esculetin, rutin, scopoletin and quercitrin) were analyzed by HPLC with a diode array detector. When the method was validated, recoveries obtained were varied from 86.9 to 96.4 % and RSDs from 3.4 to 8.2 %.